# tabla de integrales pdf - table de integrales online completa

1 Pages • 1,763 Words • PDF • 39.3 KB
Uploaded at 2021-09-24 17:11

This document was submitted by our user and they confirm that they have the consent to share it. Assuming that you are writer or own the copyright of this document, report to us by using this DMCA report button.

∫ sen (u ) du = − cos( u ) + C

6

7

a 2 + u 2 du = 2

a + u2 −

2 a4  ln u + a + u 2  + C  8 

)

(

)

(

du

)

a2 + u2 a2 + u2 du = − + ln u + a 2 + u 2 + C 2 u u du = ln u + a 2 + u 2 + C a 2 + u2 u 2 du u 2 a2 = a + u 2 − ln(u + a 2 + u 2 ) + C 2 a2 + u2 2

a2 + u2 a + a2 + u2 du = a 2 + u 2 − a ln +C u u

8

3

1 a2 + u2 + a = − ln +C 27 ∫ a u u a2 + u2

2

(a u + 2u )

(

u 2 a2 a + u 2 + ln u + a 2 + u 2 + C 2 2

2 2 2 ∫ u a + u du =

cos(u )

2

u = arc sen ( ) + C a a −u

du

2

19

∫a

2

du 1 u+a = ln +C − u 2 2a u − a du 1 u −a = ln +C 20 ∫ 2 u − a 2 2a u + a

17

du 1 u ∫ a 2 + u 2 = a arc tg( a ) + C du 1 u = arc sec( ) + C 18 ∫ 2 2 a a u u −a

16

du

2

2

2

a2 − u2

du

2

du

=−

a2 − u2 +C a 2u

1 a2 − u2 + a = − ln +C a u a −u

a −u 1 2 u du = − a − u 2 − arc sen ( ) + C u2 u a u 2 du u 2 a2 u 2 =− a − u + arc sen ( ) + C 2 2 a a2 − u2

2

40

∫u

2

3

2

2

2

4

2

2

( 2u − a u ) u − a a − ln u + u 2 − a 2 + C u − a du = − 8 8

2 2 3/ 2 ∫ (a + u ) du = −

∫u

=−

a 2 − u2 a + a2 − u2 du = a 2 −u 2 − a ln +C u u

du

(2u 3 − 5a 2 u ) a 2 − u 2 3a 4 u + arc sen ( ) + C 8 8 a du u = +C 38 ∫ 2 (a − u 2 ) 3 / 2 a 2 a 2 − u 2 u a2 2 2 2 2 2 2 39 ∫ u − a du = 2 u − a − 2 ln u + u − a + C

37

36

∫ sen(u) = ln sen(u) − sen (u ) + C 35 ∫ u

1

∫ sec( u ) du = ln sec(u ) + tg(u) + C 34 ∫

14

15

33

∫ cot g(u ) du = ln sen (u) + C

13

32

∫ tg (u ) du = ln sec( u ) + C

12

∫u

28

2

∫ sec (u ) du = tg(u ) + C

8

a2 + u2 +C 2 a 2u a2 + u2 du u 2 = +C 9 ∫ cos sec (u ) du = − cot g (u ) + C 29 ∫ 2 (a + u 2 ) 3 / 2 a 2 a 2 + u 2 u 2 a2 u 2 2 2 10 ∫ sec(u ) tg(u ) du = sec(u ) + C 30 ∫ a − u du = 2 a − u + 2 arc sen( a ) + C cot g( u ) 1 u a4 u du = − +C 11 ∫ 31 u 2 a 2 −u 2 du = (2u 2 − a 2 ) a 2 − u 2 + arc sen ( ) + C ∫ sen ( u ) sen ( u ) 8 8 a

cos(u ) du = sen (u ) + C

u

26

25

∫ a du = In(a ) a

5

1

24

u

+C

u

∫ e du = e

23

22

4

+C

+C

21

u

n +i

v du

du = 1n u + C u

n

∫ u du = n + 1u

1

∫ u dv = uv − ∫

3

2

1

Tabela de Integrais

2

2

u −a du

2

du 2

=

u2 − a2 +C a 2u u

u du

∫ a + bu

2

2b 3

[(a + bu ) − 4a (a + bu ) + 2a =

du

udu

2

2

∫ u (a + bu )

du

∫ (a + bu ) =

ln

1 1 a + bu − ln +C a (a + bu ) a 2 u

2

b

a + bu +C u a 1 = 2 + ln a + bu + C b (a + bu ) b 2

1

∫ u (a + bu ) = − au + a 2

2

]+ C

77

60

∫u

n

a + bu du =

b(2n + 3)

2 u n (a + bu )3 / 2 − na ∫ u n −1 a + bu du

[

] 80

79

+ c, se a > 0

a + bu a + bu b du du = − + ∫ u2 u 2 u a + bu

a + bu + a

a + bu − a

ln

59

a

1

78

du =

a + bu du du = 2 a + bu + a ∫ u u a + bu

a + bu

du

2

(u )du =

3

3

2

3

3

tg ( u ) + ln cos( u ) + C 2

2

[2 + cos (u)]sen (u ) + C udu =

2

[2 + sen (u)]cos( u) + C

(u )du = − cot g (u ) − u + C

( u )du = −

2

∫ tg (u )du =

∫ cos

∫ sen

3

1 1 u + sen ( 2u ) + C 2 4

( u )du = tg (u ) − u + C

2

∫ cot g

∫ tg

∫ cos

∫ sen

n

n

(u )du =

(u )du = −

3

sen n −1 (u ) cos( u ) n − 1 + sen n −2 ( u )du n n ∫

∫ cot g (u )du = −

n

( u ) du =

tg(u ) sec n −2 (u ) n − 2 + sec n −2 (u ) du n −1 n −1 ∫

∫ cos(au) cos(bu)du =

∫ sen(au) sen(bu)du =

sen (a − b)u sen (a + b)u + +C 2 (a − b ) 2(a + b)

sen (a − b) u sen (a + b)u − +C 2(a − b) 2 (a + b )

du cot g( u ) n−2 du =− + n (u ) ( n − 1)sen n −2 (u ) n − 1 ∫ sen n −2 ( u )

∫ sen

∫ sec

∫ cos

cos n −1 (u )sen (u ) n − 1 + cos n −2 (u )du n n ∫ tg n −1 (u ) 75 tg n ( u )du = − ∫ tg n −2 (u )du ∫ n −1 cot g n −1 (u ) 76 cot g n (u ) du = − − ∫ cot g n −2 (u ) du ∫ n −1 74

73

70

∫u

u n du 2u n a + bu 2na u n −1du = − ∫ b(2n − 1) b(2n + 1) a + du a + bu

cot g 2 ( u ) − ln sen ( u ) + C 2 sec( u ) tg ( u ) ln sen (u ) + tg ( u ) 71 sec 3 ( u )du = − − +C ∫ 2 2 du cot g (u ) ln cos sec( u ) − cot g ( u ) 72 ∫ =− + +C sen 3 ( u ) 2sen ( u ) 2

69

68

67

66

65

64

u − n du a + bu b(2n − 3) u − n +1du =− − n −1 a (n − 1) u 2a (n − 1) ∫ a + bu a + bu 1 1 2 63 ∫ sen (u )du = u − sen (2u ) + C 2 4

62

61

58

57

 u 2 du 1 a2  = a + bu − − 2a ln a + bu  + C 2 3 ∫ (a + bu ) b  a + bu  2 32 54 ∫ u a + bu du = (3bu − 2a )(a + bu ) + C 15b 2 udu 2 = 2 (bu − 2a ) a + bu + C 55 ∫ 3 b a + bu 2 u du 2 56 ∫ = (8a 2 + 3b 2 u 2 − 4abu) a + bu + C 3 a + bu 15b 53

52

51

50

du 1 u = ln +C 49 ∫ u (a + bu ) a a + bu

48

2

) ln a + bu

u2 − a2 u2 − a2 + ln u + u 2 − a 2 + C du = − 2 u u du = ln u + u 2 − a 2 + C u2 − a2 u 2 du u a2 = u 2 − a 2 + ln u + u 2 − a 2 + C 2 u2 − a2 2

u2 − a2 a du = u 2 − a 2 − a arc cos( ) + C u u

∫ (u

∫u

=− +C 3/ 2 − a2 a2 u2 − a2 udu 1 47 ∫ = (a + bu − a ln a + bu ) + C a + bu b 2 46

45

44

43

42

41

## Related documents

1 Pages • 1,763 Words • PDF • 39.3 KB

3 Pages • 1,349 Words • PDF • 109.2 KB

22 Pages • 17,125 Words • PDF • 3.5 MB

9 Pages • 1,477 Words • PDF • 204.6 KB

0 Pages • PDF • 364.4 KB

1 Pages • 165 Words • PDF • 6 KB

2 Pages • 495 Words • PDF • 111.9 KB

7 Pages • 1,212 Words • PDF • 305.2 KB

8 Pages • 727 Words • PDF • 3.8 MB

21 Pages • 3,504 Words • PDF • 87.6 KB